Surgical repair of complex rectovaginal fistulas: Report of two cases - Karla A. Santos Jasso; F. Antonio Medina Vega; Jorge Maza Vallejos; M. Antonieta Cabrera Hernández (Elsevier, 2017)
A rectovaginal fistula (RVF) is an abnormal communication between the rectum and the vagina. In girls, the main etiologies are iatrogenic (correction of anorrectal malformations and Hirschsprung disease) and traumatic (sexual abuse and foreign bodies). Multiple surgical approaches have been described for the treatment of this pathology, having the posterior sagital approach, in pediatric population, the one with best results. However the complex RVF (epithelialized long length communications, located at the upper third of the rectovaginal septum, diameters > 2.5 cm, and recurrent and those secondary to pelvic radiation) have poor results when are treated with conventional techniques; they require the removal of peripheral fibrous tissue and replacement by healthy tissue with adequate arterial supply, preserving the anal canal and, in consequence, fecal continence. This work describes our experience in the repair of two pediatric patients with complex rectovaginal fistulas using a combination of two colorectal surgical techniques: the posterior sagital approach and transanal pull-trough (Swenson technique) with the complete resolution of the fistulas, allowing the stomas closure and keeping fecal continence.